FILOSOFI WIRAUSAHA PROFETIK; SEBUAH REFLEKSI DALAM MERINTIS WIRAUSAHA DEWASA INI - Juhanis Juhanis (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri (UIN) Datokarama Palu, Indonesia, 2017)
The interpreneur is basically one of the keys of an economic indefendent. Everyone has dream to be successful in this case. So that, in earlier Islam had paid intention and regulated for managing an economic inprovement. In this artcile aimed at presenting the Muhammad`s consept of enterpreneur. He undoubtedly becomes a refrence of many live problems, but just very few Muslim Scholars` article which elaborates his success as an interpeneurer. It is extremely different with Western scholars that concern to examine Muhammad`s success in trade. By historcial approach, the writer concludes that the key of Muhammad`s success in improving his interpeneur really has a high relation of his a good attitude, aspecially honestly (al-amanah), clever (al-fatanah), (al-tabligh) and (al-siddiqh). Prophet Muhammad`s manegement based on these attiudes becomes known as the most succesfull an interpeneruer in the world